Inducible costimulator (ICOS) blockade inhibits accumulation of polyfunctional T helper 1/T helper 17 cells and mitigates autoimmune arthritis. Issue 8 (24th May 2010) - Frey, Oliver; Meisel, Juliane; Hutloff, Andreas; Bonhagen, Kerstin; Bruns, Lisa; Kroczek, Richard A; Morawietz, Lars; Kamradt, Thomas
Abstract : Objectives: Inducible costimulator (ICOS) and its ligand (ICOSL) regulate T and B cell responses. Glucose-6-phosphate isomerase (G6PI)-induced arthritis requires T and B lymphocytes. It was hypothesised that blocking ICOS/ICOSL interactions ameliorates G6PI-induced arthritis and reduces G6PI-specific B and T lymphocyte responses. Methods: DBA/1 mice were injected with a blocking, non-depleting anti-ICOSL monoclonal antibodies (mAbs) during the induction or effector phase of G6PI-induced arthritis. G6PI-specific antibody responses were measured by ELISA. G6PI-specific T helper (Th) cell responses were assayed by polychromatic flow cytometry. Results: Transient blockade of ICOS/ICOSL interactions profoundly reduced the severity of G6PI-induced arthritis. ELISA and proliferation assays showed no clear ex vivo correlates of protection. Polychromatic flow cytometry revealed two major findings: the absolute number of G6PI-specific Th cells was markedly diminished in secondary lymphatic organs from mice with blocked ICOS/ICOSL interactions. Within the pool of G6PI-specific Th cells the frequency of interleukin 17 (IL17), interferon γ or tumour necrosis factor α producers or polyfunctional Th cells (expressing two or more of these cytokines) was higher in treated than in control mice. Conclusions: ICOS costimulation is not mandatory for the differentiation of Th1 or Th17 cells. Instead, the lack of ICOS costimulation results in reduced survival of G6PI-specific Th cells irrespective of their functional differentiation. This study demonstrates that a thorough examination of the quantity and the quality of antigen-specific immune responses is useful to determine ex vivo correlates of efficacy for immunomodulating treatments.